The automation control system of intelligent flexible clearing robot. (28th May 2020) - Fan, Jing
The cleaning of cement warehouse is a labor-intensive and high-risk operation. The applicability and cleaning effect of traditional work tools are poor. Therefore, most of the methods are manual cleaning, which is inefficient and prone to accidents. It is of great social significance and practical value to develop an intelligent flexible warehouse cleaning robot that replaces the manual cleaning of cement. When the top of the cement warehouse is small and the volume of the cement warehouse is very large, how to ensure that the working range of the cleaning system can cover the entire area, and effectively and quickly complete the cleaning operation, and the automatic control of the cleaning robot has become an automatic control. Key issues to be addressed. Although the human–machine interface configuration technology has been widely used in automated monitoring systems, its graphical and componentized interface construction methods and the flexibility and scalability of the configuration interface have been widely recognized, but the human–machine interface, the coding method is still used in the construction, the development efficiency is low, and the interface is not open and flexible enough. At the same time, there are few research attempts on interface configuration. Interface configuration mostly only stays in the graphical phase of interface construction. Data and interactive control cannot meet the configuration requirements, and there is no complete implementation plan for configuration. Therefore, it has become an urgent need to change the traditional interface development mode and realize the configuration of man–machine interface. Based on the above background, the research content of this article is the research on the automatic control system of intelligent flexible clearing robot. Based on the understanding of the relevant properties of cement powder, this article discusses its flow state in the cement storehouse theoretically and provides a basis for subsequent structural design and stability research. A modularized and component-based configuration method for the numerical control interface is proposed. The interface is divided into three modules: data, graphics, and interactive control. The functional modules are assembled and the components are combined to implement the interface configuration. The experimental simulation results in this article show that compared to the traditional method, the amount of code editing of the configured human–machine interface is reduced by 46.34%, the development cycle is shortened by 43.72%, and the development efficiency of the configured human–machine interface has been greatly improved. It is confirmed that the configuration technology studied in this article can meet the requirements of automatic control systems.